It's good weather for more government: The effect of weather on fiscal policy - Gustavo De Souza (Federal Reserve Bank of Chicago, 2022)
I show that the weather condition on election day affects future fiscal policy. When it rains during state elections, there is an increase in the relative income of voters, which is followed by an increase in expenditure and debt. The increase in expenditure is directed towards a larger police and safety budget. This result is compatible with a model of complementarity between consumption and public goods. In the model, high-income voters support an increase in safety budget because they benefit more from it than low-income voters.
Keywords: D7; H0; H4; H7; 330; public goods; government size; fiscal policy; weather